Anh văn chuyên ngành - Nguyễn Hoàng Xuân Thảo (Trường Đại học Trà Vinh, 2020)
Unit 1. Soils. Unit 2. Repairing and improving damage soils. Unit 3. Fertilizers. Unit 4. Plants. Unit 5. Tree selection and planting. Unit 6. Trees, forests and animals. Unit 7. Insects. Unit 8. Revision. Unit 9. Agriculture policyUnit 10. Farm management.